Multidomain modelling of multichip SiC power modules - Olanrewaju, Olufisayo Abimbola (2020)
Increasing energy demands in different application fields of power electronics (e.g. Photovoltaics, Traction, Aerospace) have led to increased demand for power electronic systems with higher conversion efficiency, higher power density, reliability and higher operating temperatures among other needs. Given that power devices are an essential component of power electronic systems and their operation cuts across multiple energy domains (e.g. electrical, thermal, mechanical), efficient multidomain design of power electronic devices is crucial to meeting the increased energy demands. Simulation is a key tool for the development of novel technology and for preliminary assessment of its performance in power electronic applications. However, for simulation to be an effective tool, compromise between accuracy and computational efficiency is required.